Numerical Analysis of The Effect of Creep on The Settlement and Failure Pattern of Helical Piles Foundations - Satibi, Syawal; Fatnanta, Ferry; Aprillia. H.R., Bella (ASTONJADRO, 2025)
Peat soil is a unique type of soft soil that has a low bearing capacity and experiences significant creep effect. This inherent challenge necessitates effective improvement methods to enhance its stability, among which helical pile foundations stand out as a viable solution. Despite their promising application, the nuances of how creep influences the performance of these helical piles in peat soil remain largely unexplored. This study aims to analyse the effect of creep on the settlement and failure pattern of helical pile foundations in peat soils. Axis-symmetric two-dimensional numerical analyses using the finite element method were carried out to model helical piles foundations with varying creep indices (Cα) and differing spacings between the helical plates (1D and 3,5D). The results showed that the effect of creep caused the settlement of helical piles to increase as the value of Cα increases. However, the changes of excess pore water pressure around the helical pile foundation were not significantly affected by the variation of Cα value. In addition, the failure patterns of helical piles foundations were not affected by the creep effect, with the failure mechanism still following the cylindrical shear pattern for the 1D inter-plate spacing and the individual bearing pattern for the 3,5D inter-plate spacing. This study provides insight into the importance of considering the effect of creep in the design of helical piles foundations in peat soils for long term use.